2001
DOI: 10.1021/es0002518
|View full text |Cite
|
Sign up to set email alerts
|

Relating Ion Binding by Fulvic and Humic Acids to Chemical Composition and Molecular Size. 1. Proton Binding

Abstract: Proton binding by a soil fulvic acid, humic acid, and a set of size fractions of the humic acid was studied as a function of pH and ionic strength by potentiometric titrations. The negative charge of the humic substances resulting from deprotonation of acidic functional groups generally increased with increasing pH and increasing ionic strength. At any given pH and ionic strength, the fulvic acid fraction exhibited much higher negative charge than the humic acid fraction. For the size-fractionated humic acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 31 publications
11
71
1
Order By: Relevance
“…After the description of the PPHA data set by the NICA-Donnan model, the model has been applied successfully to the description of proton and metal ion binding data to various other humic and fulvic acids [75][76][77][78][79]. In their work, Christl et al [78,79] have shown that it was possible to reduce the number of fitting parameters if results from size exclusion chromatography and solid-state C-13 NMR spectroscopy were used to estimate two of the parameters.…”
Section: Experimental Results and Model Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the description of the PPHA data set by the NICA-Donnan model, the model has been applied successfully to the description of proton and metal ion binding data to various other humic and fulvic acids [75][76][77][78][79]. In their work, Christl et al [78,79] have shown that it was possible to reduce the number of fitting parameters if results from size exclusion chromatography and solid-state C-13 NMR spectroscopy were used to estimate two of the parameters.…”
Section: Experimental Results and Model Calculationsmentioning
confidence: 99%
“…In their work, Christl et al [78,79] have shown that it was possible to reduce the number of fitting parameters if results from size exclusion chromatography and solid-state C-13 NMR spectroscopy were used to estimate two of the parameters. Moreover, this procedure resulted in a more consistent parameter set than by fitting alone.…”
Section: Experimental Results and Model Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Humic polyelectrolytic macromolecule possess the potential to carry predominantly negative charge, at naturaly occurring pH values, due to the dissociation of acidic functional groups, mainly carboxylic and phenolic [3]. Even though there are many papers dealing with the charge development [2,[4][5][6] there is still some uncertity about how humic functional group heterogeneity affects it [7].…”
Section: Introductionmentioning
confidence: 99%